Development of Web-based system for Animal Shelter and Rescue in Johor State - Wee, Mabel; Hafit, Hanayanti; Bernard Leong (Applied Information Technology And Computer Science, 2022)
Web-based System for Animal Shelter and Rescue is a platform for animal organisations in Johor state to accumulate, as there is currently no platform that focuses this group in Malaysia. During the pandemic, several animal shelters reached out to the public for donations to care for the animals in their care, and some unscrupulous people took advantage of the opportunity to scam others. Volunteers are also in short supply at some other shelters. System prototyping is the approach used to build the proposed system. Adobe Dreamweaver was utilised as the technology, and MySQL was used as the database. This website is designed to inform the public about available animal shelters in their region, as well as to make it easier for the public to donate.